Die Anämie bei malignen Tumorerkrankungen - Aulbert, E. (Nuklearmedizin - NuclearMedicine, 1989)
Cellular uptake of 67Ga-labelled transferrin by the tumor tissue was studied in rats with tumors of different malignancy and different tumor mass using the slowly growing Morris hepatoma 5123C, the moderately growing Novikoff hepatoma and the very fast and aggressive Yoshida hepatoma AH130. The cellular accumulation of 67Ga-transferrin was found to correlate with the proliferation activity of the tumor. The 67Ga-transferrin concentration in the very fast growing Yoshida hepatoma was 4.8 times higher than the concentration in the slowly growing Morris hepatoma. The uptake of 67Ga-transferrin by the tumors resulted in a faster disappearance of circulating 67Ga-transferrin from the blood. The rate of disappearance correlated with the proliferation activity and the spread of the tumors. Using tumors of identical size the elimination of 67Ga-transferrin from the blood was much faster in the rats with Yoshida hepatoma than in those with the slowly growing Morris hepatoma. On the other hand, using tumors of different tumor size it could be demonstrated that the rate of disappearance of 67Ga-transferrin from the blood correlated directly with tumor mass. It is concluded that cellular incorporation of transferrin within the tumor cells results in a loss of circulating transferrin, which correlates with tumor mass and proliferation of tumor. This mechanism is supposed to be the cause for the hypotransferrinemia seen in patients with malignant tumors.